Statistical methods for food science : Introductory procedures for the food practitioner - Bower, John A. (Wiley Blackwell, 2013)
This book provides a source text on accessible statistical procedures for the food scientist, and is aimed at professionals and students in food laboratories where analytical, instrumental and sensory data are gathered and require some form of summary and analysis before interpretation.